2022
DOI: 10.1186/s12870-022-03754-y
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular responses of Rosa damascena mill. cv. Kashan to salicylic acid under salinity stress

Abstract: Background Today, salinity stress is one of the most important abiotic stresses in the world, because it causes damage to many agricultural products and reduces their yields. Oxidative stress causes tissue damages in plants, which occurs with the production of reactive oxygen species (ROS) when plants are exposed to environmental stresses such as salinity. Today, it is recommended to use compounds that increase the resistance of plants to environmental stresses and improve plant metabolic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…The author of the study suggests that an important precursor that occurs when endogenous salicylic acid is produced are reactive oxygen species. Thus, studies by M. Omidi et al (2022) showed the levelling of the protective effects of exogenous salicylic acid as one of the antioxidants produced under the influence of certain types of abiotic stress. N. Esmaeili et al (2021) confirms this hypothesis, as the study of the effects of salicylic acid on the main energy-transforming processes of plants are the main producers of reactive oxygen species in the plant cell and are of great interest to the scientific community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The author of the study suggests that an important precursor that occurs when endogenous salicylic acid is produced are reactive oxygen species. Thus, studies by M. Omidi et al (2022) showed the levelling of the protective effects of exogenous salicylic acid as one of the antioxidants produced under the influence of certain types of abiotic stress. N. Esmaeili et al (2021) confirms this hypothesis, as the study of the effects of salicylic acid on the main energy-transforming processes of plants are the main producers of reactive oxygen species in the plant cell and are of great interest to the scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence in the available scientific data on the involvement of salicylic acid in the development of resistance to abiotic stressors. M. Omidi et al (2022) in their research refute the fact that the accumulation of salicylic acid is an indicator of the plant's response to stress. The researchers suggest that the first indicator to be considered when examining the signalling responses of plants to abiotic stress is an increase in the generation of the active form of oxygen.…”
Section: Introductionmentioning
confidence: 95%
“…Meanwhile, APX is able to maintain the optimal level of H 2 O 2 as a signaling molecule [ 69 ]. APX is considered to be one of the main factors in reducing free radicals such as H 2 O 2 , which can minimize plant damage caused by oxidative stress [ 70 ]. APX and GPX can also convert H 2 O 2 to H 2 O and O 2 [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roses are also important in the food, pharmaceutics, and medicine industries, and are available as a broad range of cultivars and genotypes in international markets [1]. Moreover, rose petals are a natural source of fragrance and essential oils, which are valuable products in the perfume industry [2,3]. The genus Rosa covers over 200 species but only a few are being used for essential oil production.…”
Section: Introductionmentioning
confidence: 99%